Synthesis of fluorinated brassinosteroids based on alkene cross-metathesis and preliminary biological assessment - Eignerová, Barbara; Slavíková, Barbora; Budĕsínský, Milos; Dracínský, Martin; Klepetárová, Blanka; St'astná, Eva; Kotora, Martin (Journal of medicinal chemistry, 2009)
Three types of brassinosteroid analogues with perfluoroalkylated side chains were synthesized by using alkene cross-metathesis of a brassinosteroid derivative bearing a terminal alkene moiety with different (perfluoroalkyl)propenes. The presence of the double bonds in the cross-metathesis products allowed a facile one-step double dihydroxylation to provide intermediates that after Baeyer-Villiger oxidation afforded the target compounds. Biological activity of the prepared analogues was tested in GABA(A) receptor, cytotoxic, and brassinolide activity, which reached in some cases the same range as their nonfluorinated analogues.
Keywords: Alkenes; Humans; biotest; steroidy heterocyklické; halogenace; Steroids, Heterocyclic; Antineoplastic Agents; krysa rodu Rattus; lidé; cholestanoly; zvířata; potkani Wistar; steroidy; objevování léků; brassinosteroidy; alkeny; Rats, Wistar; Male; Biological Assay; Halogenation; receptory GABA-A; Brassinosteroids; nádorové buněčné linie; protinádorové látky; Rats; Animals; Cell Line, Tumor; Drug Discovery; mužské pohlaví; Steroids; Receptors, GABA-A; Cholestanols